Diagnosing Qur’ānic Precepts on Wealth Creation in Digital Age - Okanlawon, Sidiq Uthman; Zagoon-Sayeed, Haruna; Salisu, Taiwo Moshood (Invest Journal of Sharia & Economic Law, 2024)
This study examines how Islamic economic principles can provide guidance for ethical wealth creation, protection, and distribution in the rapidly evolving digital economy, particularly in the face of cybercrime and financial scams. The research investigates the adaptability of Islamic teachings to digital economic activities, emphasizing the importance of lawful enterprise and social responsibility. The study employs qualitative analysis of Qur'anic precepts, Hadiths, and contemporary Islamic scholarship. The findings reveal that Islamic wealth management principles are not only compatible with but also vital for navigating the complexities of the digital age. These principles advocate for ethical earning, robust protection of wealth through cybersecurity measures, and the socially responsible distribution of wealth. The study emphasizes the necessity for precise legal frameworks that align with Islamic ethical standards in digital commerce, alongside a strong emphasis on education regarding digital economic activities within an Islamic framework. Engaging in the digital economy under Islamic guidelines is feasible and advantageous, highlighting the critical role of international cooperation among Muslim countries to combat cybercrime and ensure a secure, equitable digital economic environment. This approach fosters economic resilience and social welfare in accordance with Islamic values.